2014
DOI: 10.1038/ncomms6126
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the NaV1.5 cytoplasmic domain by calmodulin

Abstract: Voltage gated sodium channels (Nav) underlie the rapid upstroke of action potentials (AP) in excitable tissues. Binding of channel interactive proteins is essential for controlling fast and long term inactivation. In the structure of the complex of the carboxy-terminal portion of Nav1.5 (CTNav1.5) with Calmodulin (CaM)–Mg2+ reported here both CaM lobes interact with the CTNav1.5. Based on the differences between this structure and that of an inactivated complex, we propose that the structure reported here repr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
122
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(131 citation statements)
references
References 44 publications
8
122
1
Order By: Relevance
“…1): 27 the IQ-motif allowing specific interaction with calmodulin and the PY-motif, a domain found in membrane proteins permitting the binding of ubiquitin-ligases of the Nedd4/Nedd4-like family (reviewed in 28 ). While the structural details and roles of the interaction of calmodulin and Na V 1.5 have been controversial, a recent study 29 suggested a model where calmodulin may be an essential molecular player in the transitions between the different channel states. 29 …”
Section: Sodium Channel Macromolecular Complexesmentioning
confidence: 99%
See 1 more Smart Citation
“…1): 27 the IQ-motif allowing specific interaction with calmodulin and the PY-motif, a domain found in membrane proteins permitting the binding of ubiquitin-ligases of the Nedd4/Nedd4-like family (reviewed in 28 ). While the structural details and roles of the interaction of calmodulin and Na V 1.5 have been controversial, a recent study 29 suggested a model where calmodulin may be an essential molecular player in the transitions between the different channel states. 29 …”
Section: Sodium Channel Macromolecular Complexesmentioning
confidence: 99%
“…While the structural details and roles of the interaction of calmodulin and Na V 1.5 have been controversial, a recent study 29 suggested a model where calmodulin may be an essential molecular player in the transitions between the different channel states. 29 …”
Section: Sodium Channel Macromolecular Complexesmentioning
confidence: 99%
“…However, some ionic channels tend to form clusters on cellular membrane. For different cell types from Archea to mammalian neurons, inter-channel coupling was shown to exist in these clusters (Dekker and Yellen 2006;Dixon et al 2012;Gabelli et al 2014;Huang 2006;Marx et al 1998;Marx et al 2001;Molina et al 2006;Saito et al 1988;Sonkusare et al 2014;Undrovinas and Makielski 1992).…”
Section: Cooperatively Gating Ion Channelsmentioning
confidence: 97%
“…increase in cAMP due to increasing levels of LPC at heart tissue) and the disruption of cytoskeleton due to LPC-induced ischemia, which leads to further changes in the membrane structure were suggested as possible explanations for LPC-modified cooperative gating of Na V channels. In addition to the cardiomyocyte Na V channels, a recent structural study (Gabelli et al 2014) showed that two Na V 1.5 channels can form an asymmetrical homodimer via the interactions of calmodulins that are structurally linked to the carboxy terminals of Na V 1.5 channels, forming a complex.…”
Section: Cooperatively Gating Ion Channelsmentioning
confidence: 98%
“…86 Given the homology between the Ca V and Na V channel carboxyl termini, it is reasonable to apply the structural insights gained in the Na V channel field to the Ca V channel. [110][111][112] Such comparisons of function and structure between the two channel families have created a synergistic relationship in which both fields have prospered.…”
Section: Structural Perception Changes the Meaning Of Calcium Channelmentioning
confidence: 99%